Impacts of the COVID-19 crisis on inland navigation - Bianca Borca; Lisa-Maria Putz (Adapting to the Future: How Digitalization Shapes Sustainable Logistics and Resilient Supply Chain Management. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 31, 2021)
Purpose: The goal of this paper is to provide initial insights into the impacts of the COVID-19 crisis on inland navigation on both freight and passenger transport. It creates a starting point for further research and supports practitioners to prepare for future crisis situations. Methodology: After a review of the literature, we prepared an interview guideline and conducted ten interviews with experts from the inland waterway transport (IWT) sector (i.e. freight and passenger transport). The interviews were coded and analysed using MAXQDA software. After the content analysis following the approach of Mayring (2014) we discussed the results and derived future research needs. Findings: The COVID-19 crisis has both, positive and negative impacts on inland navigation. The inland navigation sector was affected by a reduction of transport volumes, the suspension of the passenger transport and requirements for crew changes or arbitrary regulations. A positive impact is that IWT is perceived as a reliable transport mode and customer bonding increased. Originality: This paper shows initial impacts of the COVID-19 crisis for the inland navigation sector for freight and passenger transport. It provides future research needs which serve as a starting point to conduct in-depth analysis of individual impacts of the crisis.
urn:nbn:de:gbv:830-882.0161690; hdl:10419/249608; https://econpapers.repec.org/RePEc:zbw:hiclpr:31
Keywords: 650; Supply Chain Risk Management; Supply Chain Security